The Strategy for Building Religious Character Through the Boarding School Program at MAN 5 Bogor - Jubaedah, Jubaedah; Yani, Ahmad; Komalasari, Santika; Aminah, Siti (The Future of Education Journal, 2024)
This study aims to analyze the strategies for fostering religious character through the boarding school program at MAN 5 Bogor. A qualitative approach was employed, utilizing observation, interviews, and documentation for data collection. The findings reveal that the strategy is implemented through three main approaches: religious habituation, exemplary behavior, and supervision with evaluation. The program effectively cultivates disciplined, virtuous, and consistently devout students. Challenges identified include limited staff availability and initial adaptation difficulties among new students. Proposed solutions include increasing the number of staff, intensive training, and employing technology to monitor student progress. This study contributes to the development of religious character education programs tailored to the needs of boarding school students.